Manakib dalam Tradisi Masyarakat Banjar: Analisis Antropologis dengan Pendekatan Dakwah Kultural - Dahlan, Bayani; Tarwilah; Nada Rahmatina (Alhadharah: Jurnal Ilmu Dakwah, 2024)
Reading manakib is a tradition that has been carried out for generations by the Banjar people. Reading manakib is believed to be a good tradition, because religion and culture are two elements that continuously interact and influence each other. The reading of manakib from an anthropological perspective does not arise by itself, but through a long process and intersects with the concept of shifts in society and culture. This study aims to examine the meaning of manakib according to the Banjar community. This study is a field study (field research) which examines the tradition of reading manakib of figures who are believed to be Wali Allah in the beliefs of the Banjar people. Primary data in this study is information related to the tradition of reading manakib in the Banjar tradition, while secondary data is supporting information related to the study. The result of this research is that the practice of reading manakib in the Banjar community tradition is believed to be a religious practice that has social effects. People also believe that their lives will be more spacious and blessed, thus making them better individuals in living their lives. Despite the doubts and even distrust of certain parties regarding the power of manakib, Evans-Pritchard stated that the way to understand society must be from within, not through literature or observation as an outsider. In order to gain a complete understanding of a phenomenon, researchers must enter and live together with the community they are researching. The Banjar people’s reading of the manakib of Wali Allah is in line with the principle of cultural da'wah which elaborates local culture as a means of da'wah.